Potential Marker Pathways in the Endometrium That May Cause Recurrent Implantation Failure. (July 2019) - Bastu, Ercan; Demiral, Irem; Gunel, Tuba; Ulgen, Ege; Gumusoglu, Ece; Hosseini, Mohammad Kazem; Sezerman, Ugur; Buyru, Faruk; Yeh, John
The aim of this prospective cohort study was to identify altered biologic processes in the endometrium that may be potential markers of receptive endometrium in patients with repeated implantation failure (RIF) as compared with fertile controls. The study was conducted in a university-affiliated in vitro fertilization (IVF) gynecology clinic and molecular biology and genetics laboratory. Healthy fertile controls (n = 24) and patients with RIF (n = 24) were recruited. Window of implantation gene profiling associated with RIF was performed. Six hundred forty-one differentially expressed genes were identified, and 44 pathways were found enriched. Upon clustering of the enriched pathways, 9 representative pathways were established. The important pathways that were identified included circadian rhythm, pathways in cancer, proteasome, complement and coagulation cascades, citrate cycle, adherens junction, immune system and inflammation, cell cycle, and renin–angiotensin system. The involvement of the circadian rhythm pathway and other related pathways may alter the endometrium's functioning to ultimately cause RIF. Furthermore, we found that the pathogenesis of RIF was multifaceted and that numerous processes were involved. We believe that a better understanding of the underlying mechanisms of RIF will ultimately give rise to better treatment opportunities and to better outcomes in IVF.